How Contagious Were the Capitol Riots in Europe – In Praxis and in Perception? - Graaf, Beatrice de (Terrorism and political violence, 2021)
This contribution presents a short overview on the impact of the Capitol Riots riots in Europe. Fear of a similar mass-mediated contagion was explicitly expressed by most of the European leaders. Echoes and acclamation for the riots in the U.S. were indeed heard on websites, QAnon-sites, and within circles of Trump supporters in Europe as well. An earlier storming of the German Reichstag (in 2020) was cited. In the Netherlands, the curfew riots of 24–25 January 2021 also were put into this context. Security agencies and officials in the U.K. and the Netherlands repeated this threat awareness in recent, formal threat assessments.